Disappointment Aversion and Social Comparisons in a Real-Effort Competition - Simon Gächter; Lingbo Huang; Martin Sefton (Institute of Labor Economics (IZA), 2017)
We present an experiment to investigate the source of disappointment aversion in a sequential real-effort competition. Specifically, we study the contribution of social comparison effects to the disappointment aversion previously identified in a two-person real-effort competition (Gill and Prowse, 2012). To do this we compare "social" and "asocial" versions of the Gill and Prowse experiment, where the latter treatment removes the scope for social comparisons. If disappointment aversion simply reflects an asymmetric evaluation of losses and gains we would expect it to survive in our asocial treatment, while if losing to or winning against another person affects the evaluation of losses/gains we would expect treatment differences. We find behavior in social and asocial treatments to be similar, suggesting that social comparisons have little impact in this setting. Unlike in Gill and Prowse we do not find evidence of disappointment aversion.
Keywords: C91; D12; D81; D84; 330; real effort competition; social comparison effects; disappointment aversion; reference-dependent preferences